Development of an Integrated Web-Based School Information System at SMK Negeri 1 Lumban Julu - Dhea Romantika Marpaung; Muhammad Syahputra; Rizky Fadillah; Sunario Megawan; Erlina Halim (Ali Institute of Research and Publication, 2026)
Digital technology encourages schools to provide faster, more transparent, and more structured information and academic administration services. SMK Negeri 1 Lumban Julu did not yet have an integrated information system combining a public website and a role-based academic portal. This study aims to develop a web-based school information system to support school information delivery and academic data management. The system was developed using the Scrum method through requirements analysis, product backlog preparation, design, sprint implementation, and testing. The developed system provides a public website for school information, publications, departments, extracurricular activities, and tracer study, as well as an academic portal for staff, teachers, and students. Testing was conducted using blackbox testing by three prospective users, consisting of one staff member, one teacher, and one student. Testing covered 260 scenarios, consisting of 198 staff scenarios, 41 teacher scenarios, and 21 student scenarios. All scenarios were successfully executed, resulting in a functional success rate of 100%. These results indicate that the system can support integrated school information and academic data management.